Un outil pour connaître de minute en minute l’expérience d’un visiteur adulte - Dufresne-Tassé, Colette; O’Neill, Marie-Claude; Sauvé, Monique; Marin-Robitaille, Dominic (Museologia & Interdisciplinaridade, 2015)
A description of an instrument to assess the adult visitor’s experience as he lives it. It could reveal not only what he learns, but also the other benefits that he derives from strolling through an exhibition. For instance, it enables to know in details what the visitor feels and imagines, or to study phenomena like fascination and immersion.